Isolating membrane and preparation method thereof, secondary battery and electric device

CN119487688APending Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280097535.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

There are deficiencies in the thermal safety and cycle performance of batteries, which especially degrade when heated, leading to an increased risk of short circuits and reduced ion transport channels.

Method used

An isolation film including a base material and a coating is used. The coating contains granular organic materials. By controlling the unit area weight and thickness of the coating and the true density of the organic materials, the organic materials are reasonably accumulated in the coating to form The opposite squeezing force and multiple ion transmission channels improve the heat resistance and ion transmission capacity of the isolation membrane.

Benefits of technology

It effectively reduces the risk of short circuit of the battery, improves the thermal safety performance and cycle performance, while reducing the weight of the battery and improving the mass energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487688A_ABST
    Figure CN119487688A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane and a preparation method thereof, a secondary battery and a power utilization device, the isolating membrane comprises a base material and a coating, the coating is arranged on at least one side of the base material, the coating comprises an organic material, the weight per unit area of the single-side coating is marked as M, the thickness of the single-side coating is marked as H, the true density of the organic material is marked as rho organic, and the thickness of the organic material is marked as H; the unit of M is g / m < 2 >, the unit of H is [mu] m, and the unit of [mu] m is g / cm < 3 >. The isolating membrane has the characteristics of good heat resistance, ion transmission characteristic and the like, so that the thermal safety performance and the cycle performance of the battery using the isolating membrane can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Separator and preparation method thereof, secondary battery and electric device Technical Field The present application belongs to the field of battery technology, and specifically relates to an isolation membrane and a preparation method thereof, a secondary battery and an electrical device. Background Art Batteries are widely used in many fields such as power tools, electric vehicles, aerospace, energy storage equipment, etc. due to their good electrochemical performance and safety performance. With the promotion and application of batteries in many fields, their thermal safety performance and cycle performance have become two focuses of attention in battery performance. At present, the thermal safety performance of batteries still has the defect that it will decrease when heated, and its cycle performance will also decrease. Therefore, it is urgent to improve the thermal safety performance and cycle performance of batteries. Summary of the invention The purpose of the present application is to provide an isolation membrane and a preparation method thereof, a secondary battery and an electrical device. The isolation membrane has good heat resistance and ion transport properties, thereby improving the thermal safety performance and cycle performance of the secondary battery using the isolation membrane. In a first aspect, the present application provides an isolation film, comprising a substrate and a coating, wherein the coating is disposed on at least one side of the substrate, the coating comprises a granular organic material, the weight per unit area of ​​the coating on one side is denoted as M, the thickness of the coating on one side is denoted as H, and the true density of the organic material is denoted as ρ 有机 , then the isolation film satisfies: M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 . In the isolation film provided in the present application, the coating layer includes a granular organic material, and the isolation film satisfies 0.4≤M / (H×ρ 有机 ), on the one hand, it can make the organic materials in the coating accumulate reasonably. When the separator is heated, the mutual squeezing between the organic materials can provide a force opposite to the contraction direction of the separator, reduce the degree of contraction of the separator, and thus reduce the risk of short circuit between the positive and negative electrodes in the battery using the separator, so that the battery has good thermal safety performance. On the other hand, while making the organic materials accumulate reasonably in the coating, it can also make the overlap between the organic materials form more ion transmission channels, and through these ion transmission channels, the electrolyte can enhance the infiltration of the separator and the storage in the separator, which is beneficial to ion transmission, thereby improving the cycle performance of the battery. In any embodiment of the present application, 0.5≤M / (H×ρ 有机)≤0.8. The separator satisfies the above relationship, which enables the organic material to be more densely packed in the coating, thereby further reducing the shrinkage of the separator, further enabling the battery to have good thermal safety performance, and further improving the cycle performance of the battery. In any embodiment of the present application, 有机 ≤2.5. Setting the true density of the organic material within the above-mentioned suitable range can help reduce the weight of the battery using the separator, thereby improving the mass energy density of the battery. In any embodiment of the present application, 0.8≤ρ 有机 ≤2.0. In any embodiment of the present application, M≥0.5. The weight per unit area of ​​the single-sided coating satisfies the above relationship, which can further make the organic materials in the coating more densely stacked, so that adjacent organic materials overlap each other, and when the isolation film is heated, the mutual extrusion between the organic materials can provide a force in the opposite direction of the isolation film contraction, further reducing the degree of contraction of the isolation film, thereby reducing the occurrence of short circuits between the positive electrode sheet and the negative electrode sheet. In any embodiment of the present application, 0.7≤M≤3.0. In any embodiment of the present application, H≤3.0. The thickness H of the single-sided coating satisfies the above relationship, which can help the close stacking of organic materials to further improve the thermal safety performance of the battery. In any embodiment of the present application, 0.5≤H≤2.0. In any embodiment of the present application, M / H ≥ 0.3. In any embodiment of the present application, 0.5≤M / H≤1.0. In any embodiment of the present application, the mass proportion of the organic material in the coating is greater than or equal to 60%; optionally 75%-95%. In any embodiment of the present application, the organic material includes one or more of silicone particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles and polyaryletherketone particles; optionally, the organic material includes silicone particles. In any embodiment of the present application, the organic material includes organosilicon particles, the organosilicon particles include a first polymer, the first polymer includes a first structural unit, a second structural unit, and a third structural unit; The first structural unit has a structure as shown in formula (I): In formula (I), R 1Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 1 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 2 Including one or more of substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C1-C20 hydroxyalkyl; Optionally, R 2 Including one or more of C1-C12 alkyl, C3-C12 cycloalkyl, C1-C12 hydroxyalkyl; The second structural unit is shown in formula (II): In formula (II), R 3 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 3 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; The third structural unit is shown in formula (III): In formula (III), R 4 To R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, or one or more of the structural units shown in formula (III-1), wherein R 4 To R 11 At least one of them is a structural unit represented by formula (III-1), In formula (III-1), R 12 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 12 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 13 Including substituted or unsubstituted C1-C10 alkyl; Optionally, R 13 Includes substituted or unsubstituted C3-C10 alkyl groups. In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the first structural unit is denoted as a%, and 70 ≤ a ≤ 90; optionally, 75 ≤ a ≤ 85; and / or, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the second structural unit is denoted as b%, and 0 < b ≤ 18; optionally, 2 ≤ b ≤ 8; and / or, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the third structural unit is denoted as c%, and 0 < c ≤ 15; optionally, 4 ≤ c ≤ 10. In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the first structural unit is denoted as a%, the molar content of the second structural unit is denoted as b%, and the molar content of the third structural unit is denoted as c%; the silicone particles satisfy one or more of the conditions (1) to (3): (1) 5 ≤ a / b ≤ 10; (2) 6 ≤ a / c ≤ 15; (3) a:b:c is (14 - 16):(3 - 4):(1 - 4). In any embodiment of the present application, the silicone particles further include a second polymer, and the second polymer includes a structural unit represented by formula (a): In formula (a), R 14 and R 15 each independently include one or more of a substituted or unsubstituted C1 - C10 alkyl group, a hydroxyl group, or an amino group; optionally, R 14 and R 15 each independently include one or more of a substituted or unsubstituted C1 - C6 alkyl group, a hydroxyl group, or an amino group. In any embodiment of the present application, the number - average molecular weight of the silicone particles is 25,000 - 60,000, and may be 30,000 - 50,000. When the number - average molecular weight of the silicone particles is within the above range, it is beneficial to form silicone particles with smaller particle sizes. When applied to the separator membrane, it can achieve a thin coating of the coating in the separator membrane, reduce the overall thickness of the separator membrane, thereby facilitating the improvement of the energy density of the battery; and it can also reduce the risk of the silicone particles clogging the substrate in the separator membrane, achieving the purpose of improving the performance such as the overall air permeability of the separator membrane. In any embodiment of the present application, based on the mass of the silicone particles, the moisture content of the silicone particles is less than or equal to 3000 μg / g, and may be 700 μg / g - 2500 μg / g. In any embodiment of the present application, the volume distribution particle size Dv90 of the organosilicon particles satisfies: Dv90≤4.0 μm. The Dv90 of the organosilicon particles is set within the above-mentioned suitable range, which can increase its packing density while also enabling the coating to have a suitable thickness to increase the energy density of the battery. In any embodiment of the present application, the volume distribution particle size Dv90 of the silicone particles satisfies: 0.5 μ m≤Dv90≤30μm. In any embodiment of the present application, the volume distribution particle size Dv50 of the silicone particles satisfies: 1.0 μm ≤ Dv50 ≤ 2.5 μm. In any embodiment of the present application, the particle size distribution of the organosilicon particles satisfies: 0.5≤(D V 90-D V 10) / D V 50≤1.5. In any embodiment of the present application, the specific surface area of ​​the organosilicon particles is less than or equal to 35 m 2 / g, optional 5m 2 / g-30m 2 The specific surface area of ​​the organosilicon particles is set within the above-mentioned suitable range, which can increase the contact area between the organosilicon particles and the electrolyte, thereby helping to improve the wetting effect and liquid retention effect of the electrolyte on the separator. In any embodiment of the present application, the thickness of the substrate is less than or equal to 12 μm. In any embodiment of the present application, the thickness of the substrate is 3 μm-8 μm. In any embodiment of the present application, the substrate has a porous structure, and the porosity of the substrate is greater than or equal to 20%. In any embodiment of the present application, the porosity of the substrate is 25%-45%. In any embodiment of the present application, the longitudinal heat shrinkage rate of the separator at 150° C. for 1 hour is less than or equal to 3%. In any embodiment of the present application, the transverse heat shrinkage rate of the separator at 150° C. for 1 hour is less than or equal to 2%. In any embodiment of the present application, the air permeability of the isolation membrane is less than or equal to 200 s / 100 mL. In any embodiment of the present application, the air permeability of the isolation membrane is 150s / 100mL-200s / 100mL. In any embodiment of the present application, the longitudinal tensile strength of the separator is greater than or equal to 2700 kgf / cm 2 . In any embodiment of the present application, the transverse tensile strength of the separator is greater than or equal to 2500 kgf / cm2 . The second aspect of the present application provides a method for preparing the isolation film of the first aspect of the present application, comprising the following steps: Providing a substrate; The granular organic material is mixed in a solvent to prepare a coating slurry; Applying the coating slurry on at least one side of the substrate to form a slurry film layer, and drying the slurry film layer to form a coating to obtain an isolation film; The weight per unit area of ​​the single-sided coating is recorded as M, the thickness of the single-sided coating is recorded as H, and the true density of the organic material is recorded as ρ 有机 , then the isolation film satisfies: M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 . A third aspect of the present application provides a secondary battery, comprising the isolation membrane of the first aspect of the present application or the isolation membrane obtained by the preparation method of the second aspect of the present application. A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work. FIG. 1 is a schematic diagram of an embodiment of a secondary battery of the present application. FIG. 2 is an exploded schematic diagram of an embodiment of the secondary battery of FIG. 1 . FIG. 3 is a schematic diagram of an embodiment of a battery module of the present application. FIG. 4 is a schematic diagram of an embodiment of a battery pack of the present application. FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 . FIG. 6 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source. In the accompanying drawings, the drawings are not necessarily drawn according to the actual scale. The description of the accompanying drawings is as follows: 1-battery pack, 2-upper box, 3-lower box, 4-battery module, 5-battery cell, 51-shell, 52-electrode assembly, 53-cover plate. DETAILED DESCRIPTION Hereinafter, the isolation membrane and its preparation method, secondary battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims. "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application. Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc. If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included. If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). In the present application, the terms “first”, “second”, etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance. In the present application, the terms "plurality" and "multiple" refer to two or more. Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art. Unless otherwise specified, the values ​​of the parameters mentioned in the present application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the embodiments of the present application. Typically, a battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. Its main function is to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass freely to form a loop. Batteries are widely used in many fields such as power tools, electric vehicles, aerospace, energy storage equipment, etc. due to their good electrochemical performance and safety performance. With the promotion and application of batteries in many fields, their thermal safety performance and cycle performance have become two focuses of attention in battery performance. The separator is an important part of improving the thermal safety and cycle performance of the battery. The separator used in commercial batteries is usually a polyolefin porous membrane, which has a relatively low melting point. Therefore, it will have a significant thermal shrinkage effect when heated, which will not only reduce the ion transmission channel, resulting in a decrease in ion conductivity, thereby increasing the internal resistance of the battery and reducing the battery's cycle performance. In addition, the shrinkage of the separator may cause the positive and negative electrodes inside the battery to directly contact, resulting in an internal short circuit, thereby increasing the safety risk of the battery. In view of this, the present application provides an isolation membrane and a preparation method thereof, a secondary battery and an electrical device. The isolation membrane has good heat resistance and ion transport properties, thereby improving the thermal safety performance and cycle performance of the battery using the isolation membrane. Isolation film In a first aspect, the present application provides an isolation film, comprising a substrate and a coating, wherein the coating is disposed on at least one side of the substrate, the coating comprises a granular organic material, the weight per unit area of ​​the coating on one side is denoted as M, the thickness of the coating on one side is denoted as H, and the true density of the organic material is denoted as ρ 有机 , then the isolation film satisfies M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 . In the isolation film provided in the present application, the coating layer includes a granular organic material, and the isolation film satisfies M / (H×ρ 有机 )≥0.4, on the one hand, it can make the organic materials in the coating reasonably deposited, and when the separator is heated, the mutual extrusion between the organic materials can provide a force opposite to the contraction direction of the separator, reduce the degree of contraction of the separator, and thus reduce the short circuit risk of the positive and negative electrodes in the battery using the separator, so that the battery has good thermal safety performance. On the other hand, while making the organic materials reasonably deposited in the coating, it can also make the overlap between the organic materials form more ion transmission channels, and through these ion transmission channels, the electrolyte can enhance the infiltration of the separator and the storage in the separator, which is beneficial to ion transmission, thereby improving the cycle performance of the battery. In some embodiments of the present application, the isolation film satisfies: 0.5≤M / (H×ρ 有机 )≤0.8. The separator satisfies the above relationship, which enables the organic material to be more densely packed in the coating, thereby further reducing the shrinkage of the separator, further enabling the battery to have good thermal safety performance, and further improving the cycle performance of the battery. For example, M / (H×ρ 有机) can be, but is not limited to, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or a range consisting of any two of the above values. Optionally, M / (H×ρ 有机 ) can range from 0.4-0.8, 0.45-0.75, 0.5-0.7, 0.55-0.7 or 0.6-0.7. In some embodiments of the present application, the true density of the organic material is 有机 Satisfy: ρ 有机 ≤2.5. Setting the true density of the organic material within the above-mentioned suitable range can help reduce the weight of the battery using the separator, thereby improving the mass energy density of the battery. In other embodiments of the present application, the true density of the organic material is 有机 Satisfies: 0.8≤ρ 有机 ≤2.0. In some examples, the true density of the organic material is 有机 It can be, but is not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or a range consisting of any two of the above values, and can be selected from 0.1-2.5, 0.2-2.4, 0.3-2.3, 0.4-2.2, 0.5-2.1, 0.6-2.0, 0.7-1.9, 0.8-1.8, 0.9-1.7, 1.0-1.6 or 1.1-1.5. The true density of organic materials is a well-known meaning in the art and can be tested by methods known in the art. For example, the test can be performed with reference to GB / T 24586, and the specific steps can be referred to as follows: take a clean and dry sample cup and place it on a balance, reset it to zero, add the powder sample into the sample cup, which accounts for about 1 / 2 of the volume of the sample cup, record the sample mass, place the sample cup containing the sample in a true density tester, close the test system, introduce helium according to the procedure, detect the pressure of the gas in the sample chamber and the expansion chamber, and then calculate the true volume according to Bohr's law (PV=nRT), thereby calculating the true density. In some embodiments of the present application, the weight per unit area M of the single-sided coating satisfies: M≥0.5. The weight per unit area of ​​the single-sided coating satisfies the above relationship, which can further make the organic materials in the coating more densely stacked, and make adjacent organic materials overlap together. When the isolation film is heated, the mutual extrusion between the organic materials can provide a force in the opposite direction of the isolation film contraction, further reducing the degree of contraction of the isolation film, thereby reducing the occurrence of short circuits between the positive electrode sheet and the negative electrode sheet. In other embodiments of the present application, the weight M per unit area of ​​the single-sided coating satisfies: 0.7≤M≤3.0. In some examples, the weight M per unit area of ​​the single-sided coating may be, but is not limited to, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or a range consisting of any two of the above values, for example, 0.5-2.0, 0.7-2.5, 0.75-2.0, 1.0-2.5, 1.0-2.0 or 1.0-1.8. The weight per unit area of ​​the single-sided coating is well known in the art and can be tested by methods known in the art. For example, the test can be performed according to the following steps: Take a sample of the isolation film and punch it into a piece with an area of ​​S 1 Weigh the small disc and record it as M 1 Then remove the coating of the weighed sample and weigh the weight of the substrate, which is recorded as M. 0 ; ① If the substrate is coated on only one side, the weight per unit area of ​​the coating on one side = (M 1 -M 0 ) / S 1 ; ② If both sides of the substrate are coated, the weight per unit area of ​​the coating on one side = (M 1 -M 0 ) / S 1 / 2. In some embodiments of the present application, the thickness H of the single-sided coating satisfies: H≤3.0. The thickness H of the single-sided coating satisfies the above relationship, which can help the close stacking of organic materials. In this way, when the separator is heated, the close stacking of organic materials can quickly provide a force opposite to the shrinkage direction of the separator, further reducing the shrinkage degree of the separator to reduce the occurrence of short circuits between the positive electrode sheet and the negative electrode sheet, thereby achieving the purpose of improving the thermal safety performance of the battery. In other embodiments of the present application, the thickness H of the coating satisfies: 0.5≤H≤2.0. In some examples, the thickness H of the coating may be, but is not limited to, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or a range consisting of any two of the above values, for example, 0.5-2.5, 0.7-2.5, 0.8-2.8, 0.9-2.0, 1.0-2.5, 1.0-2.0. The thickness of the single-sided coating is well known in the art and can be tested using methods known in the art. For example, the thickness can be tested using a thickness meter with reference to GB / T36363-2018 standard for polyolefin separators for lithium-ion batteries. In some embodiments of the present application, the weight M per unit area of ​​the single-sided coating and the thickness H of the single-sided coating satisfy: M / H≥0.3. In some embodiments of the present application, the weight M per unit area of ​​the single-sided coating and the thickness H of the single-sided coating satisfy: 0.5≤M / H≤1.0. It should be noted that the coating parameters (such as thickness, weight per unit area, etc.) given in this application refer to the coating parameters on one side. When the coating is provided on both sides of the substrate at the same time, the coating parameters on either side satisfy this application and are considered to fall within the protection scope of this application. In some embodiments of the present application, the organic material includes one or more of silicone particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles and polyaryletherketone particles. In some optional embodiments of the present application, the organic material includes organosilicon particles. The organosilicon particles refer to organosilicon oxanes whose main chain is a silicon-oxygen-silicon bond (-Si-O-Si-). Since the silicon-oxygen-silicon bond is an inorganic bond, the bond energy is large, which can give the organosilicon very high heat resistance and chemical stability. For example, the organosilicon can be used for a long time below 200°C. The side chain of the organosilicon may not be grafted with other groups, or may be grafted with organic groups. When the organic groups are grafted, the organosilicon can be given good dispersibility, etc., which can improve the coating performance of the organosilicon coating and the affinity with the substrate. The organosilicon particles are dispersed in the coating so that the isolation film has good heat resistance, thereby improving the thermal safety performance of the secondary battery. In addition, a structure with gaps can be formed between the organosilicon particles, which can enhance the wetting and retention characteristics of the isolation film to the electrolyte, thereby promoting the transmission of active ions in the isolation film, so that the isolation film can improve the cycle performance of the secondary battery when applied to the secondary battery. In some embodiments of the present application, the organosilicon particles include a first polymer, and the first polymer includes a first structural unit, a second structural unit, and a third structural unit. The first structural unit has a structure as shown in formula (I): In formula (I), R 1 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 1 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 2 Including one or more of substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C1-C20 hydroxyalkyl; Optionally, R 2 Including one or more of C1-C12 alkyl, C3-C12 cycloalkyl, C1-C12 hydroxyalkyl; The second structural unit is shown in formula (II): In formula (II), R 3 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 3 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; The third structural unit is shown in formula (III): In formula (III), R 4 To R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, or one or more of the structural units shown in formula (III-1), wherein R 4 To R 11 At least one of them is a structural unit represented by formula (III-1), In formula (III-1), R 12 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 12 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 13 Including substituted or unsubstituted C1-C10 alkyl; Optionally, R 13 Includes substituted or unsubstituted C3-C10 alkyl groups. In the above embodiments, the first structural unit can adjust the glass transition temperature of the first polymer, improve the toughness and peel strength of the polymer, and help to exert a good bonding effect. The second structural unit can produce excellent anti-swelling and high adhesion, and then when the first polymer is applied to the isolation membrane, the first polymer is in contact with the electrolyte, and the first polymer is not easy to swell, and it has good anti-swelling properties. The third structural unit contains a skeleton structure composed of Si-O-Si or Si-O bonds, which can give the first polymer advantages in heat resistance and mechanical properties, and then during the long-term cycle charge and discharge process of the battery, the isolation membrane has good thermal stability and effectively isolates the positive and negative pole pieces, thereby ensuring the thermal safety performance of the battery. In addition, the first structural unit and the third structural unit can cooperate to improve the adhesion and heat resistance of the first polymer; the first structural unit and the second structural unit can cooperate to improve the swelling resistance of the first polymer. Therefore, the first polymer can not only improve the adhesion between the coating and the substrate, but also enhance the heat resistance of the separator to improve the thermal safety performance of the battery. In some embodiments of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is recorded as a%, 70≤a≤90. When the molar content of the first structural unit is within the above range, the adhesion of the first polymer can be significantly improved; when the first polymer is applied to the isolation membrane, the bonding force between the first polymer and the substrate of the isolation membrane can be improved. Optionally, 75≤a≤85. Exemplarily, the molar content of the first structural unit can be 70%, 75%, 80%, 85%, 90% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is recorded as b%, 0<b≤18. When the molar content of the second structural unit is within the above range, the anti-swelling property of the first polymer can be significantly improved. Optionally, 2≤b≤8. Exemplarily, the molar content of the second structural unit can be 5%, 8%, 10%, 12%, 15%, 18% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is recorded as c%, 0<c≤15. When the molar content of the third structural unit is within the above range, the heat resistance of the first polymer can be improved. Optionally, 4≤c≤10. Exemplarily, the molar content of the third structural unit can be 5%, 8%, 10%, 12%, 15% or a range consisting of any two of the above values. The first structural unit in the first polymer can give the first polymer good adhesion; however, since the first polymer will inevitably come into contact with the electrolyte when applied to the isolation membrane, the swelling effect of the electrolyte will reduce the adhesion of the first polymer to a certain extent; and the second structural unit in the first polymer, the cyano group contained in it can play a synergistic role with the first structural unit, and jointly improve the anti-swelling and adhesion of the first polymer. Therefore, when the molar content a of the first structural unit and the molar content b of the second structural unit satisfy: 5≤a / b≤10, the first structural unit can more fully play a synergistic role with the second structural unit, and improve the adhesion and anti-swelling of the first polymer. Exemplarily, a / b can be 5, 6, 7, 8 or a range consisting of any two of the above values. The first structural unit in the first polymer gives the first polymer good adhesion, but its own heat resistance is relatively poor. When the first polymer is applied to the isolation membrane, as the battery charging and discharging time increases, the temperature in the battery increases, which may cause the first structural unit to be destroyed; and the first polymer also includes a third structural unit. The inorganic structure of polysilsesquioxane in the third structural unit can synergize with the first structural unit to improve the overall heat resistance and adhesion of the first polymer. Therefore, when the molar content a of the first structural unit and the molar content c of the third structural unit satisfy: 6≤a / c≤15, the first structural unit can more fully synergize with the third structural unit to improve the adhesion and heat resistance of the first polymer. Exemplarily, a / c can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of the above values. In some embodiments of the present application, the degree of polymerization a of the first structural unit, the degree of polymerization b of the second structural unit, and the degree of polymerization c of the third structural unit satisfy: a:b:c=(14-16):(3-4):(1-4). When the degrees of polymerization of the first structural unit, the second structural unit, and the third structural unit satisfy the above ratio, the three structural units in the organosilicon particles can cooperate with each other on the basis of exerting their respective performance advantages, and jointly improve the adhesion, thermal stability, and anti-swelling properties of the polymer. The first structural unit includes a variety of chemical structures, and the specific chemical structure of the first structural unit is described below. In some embodiments of the present application, R 1 Includes hydrogen atoms and / or methyl groups. In some embodiments of the present application, R 2 The alkyl radicals include one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl, 2-ethylhexyl, dodecyl and isobornyl. Illustratively, the first structural unit includes one or more of the structures represented by formula (I-1) to the structures represented by formula (I-8): The second structural unit includes a variety of chemical structures, and the specific chemical structure of the second structural unit is described below. In some embodiments of the present application, R 3 Includes hydrogen atoms and / or methyl groups. Illustratively, the second structural unit includes one or more of the structures represented by formula (II-1) to the structures represented by formula (II-4): The third structural unit includes a variety of chemical structures, and the specific chemical structure of the third structural unit is described below. In some embodiments of the present application, R 4 To R 11 Each independently comprises a structural unit as shown in formula (III-1); optionally, R 12 includes one or more of a hydrogen atom, a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, a tert-butyl group or a n-pentyl group; and / or, R 13 The present invention includes one or more of n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl or 2-ethylhexyl. In the present application, the type of group in the first polymer can be determined by infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks contained therein, thereby determining the type of the modified group. Specifically, the material can be subjected to infrared spectroscopy analysis using instruments and methods known in the art, such as an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet, USA), and tested according to the general rules for infrared spectroscopy analysis methods of GB / T 6040-2019. In some embodiments of the present application, the first polymer has a wavelength of 1750 cm -1 Up to 1735cm -1 , which indicates the presence of an ester group. In some embodiments of the present application, the first polymer has a wavelength of 2260 cm in the infrared spectrum. -1 Up to 2220cm -1 , which indicates the presence of a cyano group. In some embodiments of the present application, the first polymer has an infrared spectrum of 1100 nm. -1 Up to 1120cm -1, which indicates the presence of the Si-O-Si skeleton of silsesquioxane. In some embodiments of the present application, the first polymer can be prepared by the following method, which includes: Step S100, providing a first monomer, a second monomer and a third monomer; Step S200 , mixing the first monomer, the second monomer and the third monomer, and causing a polymerization reaction under the action of an initiator to generate a first polymer. In the present application, the first monomer, the second monomer and the third monomer are mixed and copolymerized, and the formed first polymer is a copolymer of the three monomers. The first monomer has a structure represented by formula (IV), In formula (IV), R 1 is selected from a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; optionally, R 1 is selected from a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 2 is selected from substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C1-C20 hydroxyalkyl; optionally, R 2 Selected from C1-C12 alkyl, C3-C12 cycloalkyl, C1-C12 hydroxyalkyl. The first monomer is an acrylic acid ester compound, and when it is polymerized, the carbon-carbon double bond opens to form a first structural unit. Illustratively, the first monomer includes one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. The second monomer has a structure represented by formula (V), In formula (V), R 3 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 3 It includes one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group. The second monomer is an acrylonitrile compound, and when it is polymerized, the carbon-carbon double bond opens to form a second structural unit. Illustratively, the second monomer includes acrylonitrile and / or methacrylonitrile. The third monomer has a structure shown in formula (VI), In formula (VI), R 30 To R 37 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, or one or more of the structural units shown in formula (VI-1), wherein R 30 To R 37 At least one of them is a structural unit represented by formula (VI-1), In formula (VI-1), R 12 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 12 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 13 Including substituted or unsubstituted C1-C10 alkyl; Optionally, R 13 Includes substituted or unsubstituted C3-C10 alkyl groups. Exemplarily, the third monomer includes one or more of methacryloxypropyl cage polysilsesquioxane, methacryloxypropyl heptaisobutyl polysilsesquioxane, methacryloxypropyl heptaoctyl polysilsesquioxane, acryloxypropyl cage polysilsesquioxane, acryloxypropyl heptaisobutyl polysilsesquioxane and methacryloxypropyl heptaoctyl polysilsesquioxane. In some implementations of the present application, step S200 specifically includes: Step S210, adding a first monomer, a second monomer and a third monomer into a solvent and an emulsifier and mixing them to form a mixed system; Step S220, adding an initiator to the mixed system, and causing a polymerization reaction under the action of the initiator to generate a first polymer. The present application can copolymerize multiple monomers by emulsion polymerization, and the polymerization method is simpler. Of course, the present application can also adopt other polymerization methods, such as solution polymerization, suspension polymerization, etc. The process parameters used in the polymerization process can be selected from the commonly used parameters in the field, which will not be repeated here.

[0155] In some embodiments of the present application, the emulsifier includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, alkyl diphenyl oxide disulfonate, and ethoxylated alkylphenol ammonium sulfate.

[0156] In some embodiments of the present application, based on the total mass of the mixed system, the ratio of the mass percentage of the emulsifier to the mass percentage of the first monomer, the second monomer and the third monomer is 0.1% to 5%, that is, the amount of the emulsifier is 0.1% to 5% of the mass of the three monomers. When the mass percentage of the emulsifier is within the above range, the first monomer, the second monomer and the third monomer can be emulsified and dispersed in the solvent to form a relatively uniform system.

[0157] In some embodiments of the present application, the initiator includes potassium persulfate and / or ammonium persulfate.

[0158] In some embodiments of the present application, based on the total mass of the mixed system, the ratio of the mass percentage of the initiator to the mass percentage of the second monomer, the second monomer and the third monomer is 0.15% to 1%, that is, the amount of the initiator is 0.1% to 5% of the mass of the three monomers. When the mass percentage of the initiator is within the above range, sufficient polymerization can be guaranteed. In some embodiments of the present application, the solvent may include water such as deionized water. As a specific embodiment, the method includes: Preparation of prepolymer: deionized water, emulsifier, first polymerizable monomer, second polymerizable monomer and third polymerizable monomer are mixed and stirred uniformly to obtain prepolymer; Preparation of the first polymer: add an emulsifier and deionized water into a container, stir and emulsify for 30 to 60 minutes to obtain a uniform and stable emulsion; then slowly drop the prepolymer and initiator solution prepared in the step (dissolve the initiator potassium persulfate and / or ammonium persulfate in deionized water to form a solution), and after the dropwise addition is completed, heat to 90° C. to 110° C. and keep the temperature for 0.5 h, cool to 40° C., adjust the pH to 7 to 8 with ammonia water, filter, discharge, and obtain a polymer through a drying process. In some embodiments of the present application, the organosilicon particles further include a second polymer, and the second polymer includes a structural unit represented by formula (a): In formula (a), R 14 and R 15 Each is independently selected from substituted or unsubstituted C1-C10 alkyl, hydroxyl or amino. 14 and R 15 Each is independently selected from substituted or unsubstituted C1-C6 alkyl, hydroxyl or amino. Exemplarily, the organosilicon particles include at least one of the structures shown in formula (a-1) to the structures shown in formula (a-5): The first polymer and the second polymer in the present application are only used to distinguish the types of materials, and have no limiting effect on the order and quantity. In some embodiments of the present application, the number average molecular weight of the organosilicon particles is 25000-60000, and can be optionally 30000-50000. Exemplarily, the number average molecular weight of the organosilicon particles can be 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000 or a range consisting of any two of the above values. When the number average molecular weight of the organosilicon particles is within the above range, they have a relatively high viscosity, which is beneficial to improve the bonding force between the isolation membrane and the positive and negative pole pieces when the organosilicon particles are applied to the isolation membrane. When the number average molecular weight of the organosilicon particles is within the above range, it is beneficial to form organosilicon particles with a smaller particle size. When applied to the isolation membrane, it can achieve a thin coating of the coating in the isolation membrane, reduce the overall thickness of the isolation membrane, and thus facilitate the improvement of the energy density of the secondary battery; and the particle size of the organosilicon particles formed by the organosilicon particles will not be too small, which can reduce the risk of the organosilicon particles blocking the substrate in the isolation membrane, and can improve the overall air permeability and other properties of the isolation membrane. In the present application, the number average molecular weight of the first polymer can be tested by gel permeation chromatography (GPC). Specifically, the GPC1515 instrument of Waters Company of the United States is used for testing, the sample is dissolved in tetrahydrofuran, the dissolution time is more than 12 hours, the concentration of the sample is 4 mg / mL, the sample is filtered, the test temperature is 25°C, and the test flow rate is 1 ml / min for testing. The inventors further discovered that during the long-term charge and discharge process of the battery, the moisture in the isolation membrane will gradually be released and enter the electrolyte, and the electrolyte is highly sensitive to moisture and easily produces hydrofluoric acid HF when it comes into contact with water, thereby increasing the acidity of the electrolyte, causing corrosion of active materials and current collectors, etc., and may cause the dissolution of transition metal ions in the active materials, thereby affecting the electrochemical performance of the battery. Therefore, the present application regulates the moisture content of the organosilicon particles to be less than or equal to 3000μg / g, and can be selected as 700μg / g-2500μg / g, based on the mass of the organosilicon particles. When the moisture content of the organosilicon particles is within the above range, the moisture content contained therein is relatively small, and during the long-term charge and discharge cycle of the battery, the risk of side reactions in the electrolyte can be reduced, thereby improving the electrochemical performance of the battery. Illustratively, the moisture content of the organosilicon particles may be 700 μg / g, 800 μg / g, 1000 μg / g, 1200 μg / g, 1500 μg / g, 1800 μg / g, 2000 μg / g, 2500 μg / g, 3000 μg / g or a range consisting of any two of the above values. In the present application, the moisture content of the organosilicon particles can be measured by a moisture meter, the test method can adopt the Karl Fischer moisture determination method, and the test instrument can adopt the Swiss Metrohm 831 Karl Fischer moisture meter. In some embodiments of the present application, the volume distribution particle size Dv90 of the organosilicon particles satisfies: Dv90≤2.0 μm. The Dv90 of the organosilicon particles is set within the above-mentioned suitable range, which can increase its packing density while also enabling the coating to have a suitable thickness to increase the energy density of the battery. In other embodiments of the present application, the volume distribution particle size Dv90 of the silicone particles satisfies: 0.5 μm ≤ Dv90 ≤ 1.5 μm. In some examples, the volume distribution particle size Dv90 of the silicone particles can be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, or a range consisting of any two of the above values. In some embodiments of the present application, the volume distribution particle size Dv50 of the organosilicon particles satisfies: 1.0 μm ≤ Dv50 ≤ 2.5 μm; In some embodiments of the present application, the particle size distribution of the silicone particles satisfies: 0.5≤(D V 90-D V 10) / D V 50≤1.5. In this application, the volume distribution particle size Dv90 of the material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 90%, and can be measured using instruments and methods known in the art. For example, it can be tested with a laser particle size analyzer (such as Master Size 3000) with reference to GB / T 19077-2016 particle size distribution laser diffraction method. In this application, the volume distribution particle size Dv50 of the material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be tested with a laser particle size analyzer (such as Master Size 3000) with reference to GB / T 19077-2016 particle size distribution laser diffraction method. In this application, the volume distribution particle size Dv10 of the material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%, and can be measured using instruments and methods known in the art. For example, it can be tested with a laser particle size analyzer (such as Master Size 3000) with reference to GB / T 19077-2016 particle size distribution laser diffraction method. In some embodiments of the present application, the specific surface area of ​​the organosilicon particles is less than or equal to 35 m 2 / g, optional 5m 2 / g-30m 2 The specific surface area of ​​the organosilicon particles is set within the above-mentioned suitable range, which can increase the contact area between the organosilicon particles and the electrolyte, thereby helping to improve the wetting effect and liquid retention effect of the electrolyte on the separator. In the present application, the specific surface area of ​​the particles is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method. Alternatively, the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA. In some examples, the specific surface area of ​​the silicone particles may be, but is not limited to, 3 m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 10.5m 2 / g, 11m 2 / g, 11.5m 2 / g, 12m 2 / g, 12.5m 2 / g, 13m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.5m 2 / g, 15m 2 / g, 15.5m 2 / g, 16m 2 / g, 16.5m 2 / g, 17m 2 / g, 17.5m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g, 27m 2 / g, 28m 2 / g, 29m 2 / g, 30m 2 / g, 31m 2 / g, 32m 2 / g, 33m 2 / g, 34m 2 / g, 35m 2 / g or a range consisting of any two of the above values. In some embodiments of the present application, the thickness of the substrate is less than or equal to 12 μm. Optionally, the thickness of the substrate is 3 μm-8 μm. The coating of the present application can improve the thermal safety performance and cycle performance of the isolation membrane, thereby allowing a thinner substrate to be selected, thereby helping to further improve the energy density of the battery. In some embodiments of the present application, the substrate has a porous structure, and the porosity of the substrate is greater than or equal to 20%. Optionally, the porosity of the substrate is 25%-45%. When the porosity of the porous substrate is within the above-mentioned suitable range, it is beneficial to further improve the ion transport characteristics of the separator to improve the cycle performance of the battery. The present application has no particular restrictions on the material of the substrate, and any known substrate with good chemical stability and mechanical stability can be selected. For example, the substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The porous substrate may be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer may be the same or different. In some embodiments of the present application, the longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is less than or equal to 3%. In some embodiments of the present application, the transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is less than or equal to 2%. In the above embodiments, the isolation film of the present application has low thermal shrinkage in both the transverse and longitudinal directions, thereby further improving the thermal safety performance of the battery. In some embodiments of the present application, the air permeability of the separator is less than or equal to 200s / 100mL. Optionally, the air permeability of the separator is 150s / 100mL-200s / 100mL. The separator of the present application has good air permeability, thereby improving the ion transport characteristics, reducing the resistance of the battery, and improving the cycle performance of the battery. In some embodiments of the present application, the longitudinal tensile strength of the separator is greater than or equal to 2700 kgf / cm 2 . In some embodiments of the present application, the transverse tensile strength of the separator is greater than or equal to 2500 kgf / cm 2 . In the above-mentioned embodiments, the isolation membrane of the present application has high tensile strength in both the transverse and longitudinal directions, so that when the battery expands, the isolation membrane is less likely to be damaged, thereby further improving the safety performance of the battery. In the present application, the heat shrinkage, tensile strength and air permeability of the isolation film have the meanings known in the art and can be measured by methods known in the art. For example, they can be tested with reference to the standard GB / T 36363-2018. It should be noted that the coating parameters of the above isolation membranes are all coating parameters on one side of the substrate. When the coating is disposed on both sides of the substrate, the coating parameters on either side satisfy the requirements of this application and are considered to fall within the protection scope of this application. Preparation method of isolation film The second aspect of the present application provides a method for preparing the isolation film of the first aspect of the present application, comprising the following steps: S1, providing a substrate; S2, mixing a granular organic material in a solvent to prepare a coating slurry; S3, coating the coating slurry on at least one side of the substrate to form a slurry film layer, and drying the slurry film layer to form a coating to obtain an isolation film; wherein the weight per unit area of ​​the single-side coating is recorded as M, the thickness of the single-side coating is recorded as H, and the true density of the organic material is recorded as ρ 有机 , then the isolation film satisfies: M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 . In some embodiments of the present application, in S2, the solvent may be water, such as deionized water. The binder may be an aqueous solution binder, which has the advantages of good thermodynamic stability and environmental protection, thereby facilitating the preparation and coating of the coating slurry. As an example, the aqueous solution binder may include at least one of an aqueous solution type acrylic resin (e.g., acrylic acid, methacrylic acid, sodium acrylate monomer homopolymer or copolymer with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymer and polyacrylamide. In addition, the coating slurry may also include other components, for example, a dispersant, a wetting agent, etc. may also be included. In some embodiments of the present application, in S3, coating is performed using a coating machine. The present application has no particular restrictions on the model of the coating machine, for example, a commercially available coating machine can be used. Optionally, the coating machine includes a gravure roller, which is used to transfer the coating slurry to the substrate. Optionally, the line number of the gravure roller is 100LPI-200LPI, and more preferably 150LPI-180LPI. In addition, the coating method can be transfer coating, spin spraying, dip coating, etc. In some embodiments of the present application, in S3, the coating speed can be controlled between 30m / min-120m / min, for example, between 60m / min-90m / min. When the coating speed is within the above range, the film surface problem of the coating can be effectively reduced and the probability of uneven coating can be reduced, thereby further improving the energy density and safety performance of the battery. By controlling the above process parameters within the given range, the performance of the isolation membrane of the present application can be further improved. Those skilled in the art can selectively adjust one or more of the above process parameters according to actual production conditions. The preparation method of the isolation film of the present application obtains the coating layer by one-time coating, which greatly simplifies the production process of the isolation film. Some raw materials and their contents used in the preparation method of the isolation membrane of the present application can refer to the isolation membrane of the first aspect of the embodiment of the present application, and will not be repeated here. Unless otherwise specified, all raw materials used in the preparation method of the isolation membrane of the present application can be obtained commercially. Secondary battery The third aspect of the embodiment of the present application provides a secondary battery. A secondary battery, also known as a rechargeable battery or storage battery, refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Generally, a secondary battery includes an electrode assembly and an electrolyte, and the electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium ion battery, a sodium ion battery, etc. In particular, the secondary battery may be a lithium ion secondary battery. The secondary battery of the present application comprises the separator of the first aspect of the present application or the separator obtained by the preparation method of the second aspect of the present application, and the separator is spaced between the positive electrode sheet and the negative electrode sheet. Optionally, at least one side of the separator close to the negative electrode sheet has the coating of the present application. As a result, the secondary battery of the present application has good thermal safety performance and cycle performance. [Positive electrode] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two opposite sides in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector. When the secondary battery of the present application is a lithium ion secondary battery, the positive electrode active material may include but is not limited to at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate and their respective modified compounds. Examples of lithium transition metal oxides may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their respective modified compounds. Examples of lithium-containing phosphates may include but are not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their respective modified compounds. In some embodiments of the present application, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion secondary battery may include a general formula of Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from at least one of N, F, S and Cl. As an example, a positive electrode active material for a lithium ion secondary battery may include LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 、LiFePO 4 、LiMnPO 4 At least one of . When the secondary battery of the present application is a sodium ion secondary battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials. As an example, a positive electrode active material for a sodium ion secondary battery may include NaFeO 2 、NaCoO 2 、NaCrO 2 、NaMnO 2 、NaNiO 2 、NaNi 1 / 2 Ti 1 / 2 O 2 、NaNi 1 / 2 Mn 1 / 2 O 2 、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O 2 、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、NaFePO 4 、NaMnPO 4 、NaCoPO 4 , Prussian blue materials, general formula X p M' q (PO 4 ) r O x Y 3-x In the general formula X p M'q (PO 4 ) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X is selected from H + , Li + 、Na + , K + and NH 4 + At least one of, M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br. In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification of the positive electrode active materials. In some embodiments of the present application, the positive electrode film layer may further optionally include a positive electrode conductive agent. The present application has no particular restrictions on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments of the present application, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤6wt%. In some embodiments of the present application, the positive electrode film layer may also optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments of the present application, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5wt%. In some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one side of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE). The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto. [Negative electrode] In some embodiments of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two opposite sides in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material may adopt the negative electrode active material for secondary batteries known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material. In some embodiments of the present application, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments of the present application, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤7wt%. In some embodiments of the present application, the negative electrode film layer may also optionally include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments of the present application, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤6wt%. In some embodiments of the present application, the negative electrode film layer may also optionally include other additives. As an example, the other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. In some embodiments of the present application, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤3wt%. In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one side of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE). The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto. The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer. [Electrolyte] During the charge and discharge process of the secondary battery, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs. The electrolyte includes electrolyte salt and solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to actual needs. When the secondary battery of the present application is a lithium ion secondary battery, as an example, the electrolyte salt may include but is not limited to lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), at least one of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). When the secondary battery of the present application is a sodium ion secondary battery, as an example, the electrolyte salt may include but is not limited to sodium hexafluorophosphate (NaPF 6 ), sodium tetrafluoroborate (NaBF 4 ), sodium perchlorate (NaClO 4 ), sodium hexafluoroarsenate (NaAsF 6 ), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO 2 F 2 ), at least one of sodium difluorooxalate phosphate (NaDFOP) and sodium tetrafluorooxalate phosphate (NaTFOP). As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). In some embodiments of the present application, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery. In some embodiments of the present application, the positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly through a winding process and / or a lamination process. In some embodiments of the present application, the secondary battery may further include an outer package, which may be used to package the electrode assembly and the electrolyte. In some embodiments of the present application, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS). The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. FIG1 is a secondary battery 5 of a square structure as an example. In some embodiments of the present application, as shown in FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film may form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 may be one or more, which can be adjusted according to demand. The preparation method of the secondary battery of the present application is well known. In some embodiments of the present application, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and a secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes. In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module. FIG3 is a schematic diagram of a battery module as an example. As shown in FIG3 , in a battery module 4, a plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space. In some embodiments of the present application, the above-mentioned battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack. FIG4 and FIG5 are schematic diagrams of a battery pack 1 as an example. As shown in FIG4 and FIG5, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner. Electrical devices The fourth aspect of the embodiments of the present application provides an electrical device, which includes at least one of the secondary battery, battery module or secondary battery pack of the third aspect of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc. The electric device can select a secondary battery, a battery module or a battery pack according to its usage requirements. Fig. 6 is a schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used. As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source. The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available. Example 1 Preparation of silicone particles Preparation of prepolymer: 300 g of deionized water and 1.5 g of sodium dodecyl sulfate were added to a 5L three-necked flask, and the mixture was stirred and emulsified at a speed of 1500 r / min for 30 min to obtain a uniform and stable emulsion, and then 137.74 g of methyl acrylate, 15.9 g of acrylonitrile and 66.35 g of methacryloyloxypropyl cage-type polysilsesquioxane (the molar content ratio of methyl acrylate, acrylonitrile and methacryloyloxypropyl cage-type polysilsesquioxane was 16:3:1) were added in sequence, and stirring was continued at a speed of 1500 r / min for 30 min to obtain a uniform prepolymer. Preparation of organosilicon particles: In a dry three-necked flask, add 0.6g of sodium dodecyl sulfate and 200g of deionized water, stir at high speed for 30min to emulsify, and obtain a uniform and stable emulsion; then use a peristaltic pump to slowly drop the prepolymer and initiator solution prepared in the previous step (dissolve 0.6g of potassium persulfate in 10g of deionized water to form a solution), and after the addition is completed, heat to 90°C and keep warm for 0.5h, cool to 40°C, adjust the pH to 7-8 with ammonia water, filter, discharge, and obtain organosilicon particles with a number average molecular weight of 25473 through a drying process, which are recorded as O1, and the water content of O1 is 1000μg / g, the volume distribution particle size Dv90 is 1.5μm, the volume distribution particle size Dv50 is 1.2μm, the volume distribution particle size Dv10 is 0.4μm, and the specific surface area is 20m 2 / g. Preparation of isolation membrane Provide PE substrate: thickness 6μm, porosity 30%. Preparation of coating slurry: Mix the organosilicon particles O1 and polyvinyl alcohol in water in a proportion (mass ratio of 8:2) to prepare a coating slurry. Coating: The prepared coating slurry is coated on both sides of the PE substrate by a coating machine, and a separator is obtained through drying and slitting processes. Preparation of positive electrode The active material LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), conductive agent acetylene black, and binder polyvinylidene fluoride are uniformly mixed in a proper amount of solvent N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting. Preparation of negative electrode The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting. Preparation of electrolyte Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 30:70 to obtain an organic solvent. 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Preparation of battery cells The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a battery cell is obtained. Examples 2 to 12 The battery cell is prepared by a method similar to that of Example 1, except for the relevant parameters of the coating of the isolation membrane. In Example 10, the type of organic silicon particles is different from that of other examples. The specific parameters are shown in Table 1. In Example 10, the preparation method of the organosilicon particles is as follows: Preparation of prepolymer: 1400g of deionized water and 7g of sodium dodecyl sulfate were added to a 5L three-necked flask, and the mixture was stirred and emulsified at a speed of 1500r / min for 30min to obtain a uniform and stable emulsion, and then 645.68g of methyl acrylate, 75.59g of acrylonitrile and 663.50g of methacryloyloxypropyl cage-type polysilsesquioxane (the molar content ratio of methyl acrylate, acrylonitrile and acryloxypropyl cage-type polysilsesquioxane was 15:3:2) were added in sequence, and stirring was continued at a speed of 1500r / min for 30min to obtain a uniform prepolymer. Preparation of organosilicon particles: In a dry three-necked flask, add 3g of sodium dodecyl sulfate and 1000g of deionized water, stir at high speed for 30min to emulsify, and obtain a uniform and stable emulsion; then use a peristaltic pump to slowly drop the prepolymer and initiator solution prepared in the previous step (dissolve 3g of potassium persulfate in 30g of deionized water to form a solution), and after the addition is completed, heat to 90°C and keep warm for 0.5h, cool to 40°C, adjust the pH to 7-8 with ammonia water, filter, discharge, and obtain organosilicon particles with a number average molecular weight of 39529 through a drying process, which are recorded as O2, and the water content of O2 is 1500μg / g, the volume distribution particle size Dv90 is 1.8μm, the volume distribution particle size Dv50 is 1.2μm, the volume distribution particle size Dv10 is 0.6μm, and the specific surface area is 10m 2 / g. Comparative Example 1 The battery cell is prepared by a method similar to that of Example 1, except that the coating parameters of the isolation film, such as the material of the particles and M / (H·ρ 有机 ), the specific parameters are shown in Table 1. Test Section (1) Thermal shrinkage test of isolation film Sample preparation: The isolation film prepared above was punched into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on A4 paper and fixed. The A4 paper containing the samples was then placed on corrugated paper with a thickness of 1 mm to 5 mm. Sample test: Place the A4 paper on the corrugated paper into a blast oven. Set the temperature of the blast oven to 150°C. After the temperature reaches the set temperature and stabilizes for 30 minutes, start timing. After 1 hour, measure the length and width of the isolation film. The values ​​are marked as a and b respectively. Calculation of thermal shrinkage: longitudinal (MD) thermal shrinkage = [(100-a) / 100] × 100%, transverse (TD) thermal shrinkage = [(50-b) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result. (2) Battery capacity retention test At 25°C, charge at 1 / 3C constant current to 4.3V, then charge at 4.3V constant voltage to current 0.05C, leave for 5 minutes, then discharge at 1 / 3C to 2.8V. The resulting capacity is recorded as the initial capacity C 0 . And record the discharge capacity C of the battery after the 1000th cycle 1000 , then the battery capacity retention rate P after each cycle 1000 =C 1000 / C 0 *100%. Table 1 lists the test results of the coatings in Examples 1-12 and Comparative Example 1 under different parameters. Table 1 According to Table 1, by comparing the test results of Examples 1-12 and Comparative Example 1, it can be seen that the coating includes a granular organic material, and the isolation film satisfies M / (H×ρ 有机 )≥0.4, on the one hand, it can make the organic materials in the coating reasonably deposited, and when the separator is heated, the mutual extrusion between the organic materials can provide a force opposite to the contraction direction of the separator, reduce the degree of contraction of the separator, and thus reduce the short circuit risk of the positive and negative electrodes in the battery using the separator, so that the battery has good thermal safety performance. On the other hand, while making the organic materials reasonably deposited in the coating, it can also make the overlap between the organic materials form more ion transmission channels, and through these ion transmission channels, the electrolyte can enhance the infiltration of the separator and the storage in the separator, which is beneficial to ion transmission, thereby improving the cycle performance of the battery. It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A separator membrane, comprising: a substrate; and a coating disposed on at least one side of the substrate, the coating comprising particulate organic material; The weight per unit area of ​​the coating on one side is recorded as M, the thickness of the coating on one side is recorded as H, and the true density of the organic material is recorded as ρ 有机 , then the isolation film satisfies: M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 .

2. The isolation film according to claim 1, wherein: 0.5≤M / (H×ρ 有机 )≤0.8。 3. The isolation film according to claim 1 or 2, wherein: ρ 有机 ≤2.5; optionally, 0.8≤ρ 有机 ≤2.

0.

4. The isolation film according to any one of claims 1 to 3, wherein: M ≥ 0.5; optionally, 0.7 ≤ M ≤ 3.

0.

5. The isolation film according to any one of claims 1 to 4, wherein: H ≤ 3.0; optionally, 0.5 ≤ H ≤ 2.

0.

6. The isolation film according to any one of claims 1 to 5, wherein: M / H ≥ 0.3; optionally, 0.5 ≤ M / H ≤ 1.

0.

7. The isolation film according to any one of claims 1 to 6, wherein: The mass proportion of the organic material in the coating is greater than or equal to 60%; optionally 75% - 95%.

8. The isolation film according to any one of claims 1 to 7, wherein: The organic material comprises one or more of silicone particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamideimide particles, polyaramide particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, and polyaryletherketone particles; Optionally, the organic material comprises silicone particles.

9. The isolation film according to any one of claims 1 to 8, wherein: The organic material comprises silicone particles, and the silicone particles comprise a first polymer, the first polymer comprising a first structural unit, a second structural unit, and a third structural unit; The first structural unit has the structure shown in formula (I): In formula (I), R1 comprises a hydrogen atom, or one or more of substituted or unsubstituted C1-C5 alkyl groups; optionally, R1 comprises a hydrogen atom, or one or more of substituted or unsubstituted C1-C3 alkyl groups; R2 comprises one or more of substituted or unsubstituted C1-C20 alkyl groups, substituted or unsubstituted C3-C20 cycloalkyl groups, substituted or unsubstituted C1-C20 hydroxyalkyl groups; optionally, R2 comprises C1-C12 alkyl groups, C3-C12 cycloalkyl groups, C1-C12 hydroxyalkyl groups; The second structural unit is shown in formula (II): In formula (II), R3 comprises a hydrogen atom, or one or more of substituted or unsubstituted C1-C5 alkyl groups; optionally, R3 comprises a hydrogen atom, or one or more of substituted or unsubstituted C1-C3 alkyl groups; The third structural unit is shown in formula (III): In formula (III), R4 to R 11 Each independently comprises a substituted or unsubstituted C1-C10 alkyl group, or one or more of the structural units shown in formula (III-1), and R4 to R 11 At least one of them is a structural unit represented by formula (III-1), In formula (III-1), R 12 Including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C5 alkyl group; Optionally, R 12 including one or more of a hydrogen atom, or a substituted or unsubstituted C1-C3 alkyl group; R 13 Including substituted or unsubstituted C1-C10 alkyl; Optionally, R 13 This includes substituted or unsubstituted C3-C10 alkyl groups.

10. The isolation film according to claim 9, wherein: Based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the first structural unit is denoted as a%, 70 ≤ a ≤ 90; optionally, 75 ≤ a ≤ 85; and / or Based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the second structural unit is denoted as b%, 0 < b ≤ 18; optionally, 2 ≤ b ≤ 8; and / or Based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the third structural unit is denoted as c%, 0 < c ≤ 15; optionally, 4 ≤ c ≤ 10.

11. The isolation membrane according to claim 9 or 10, wherein: Based on the total molar amount of the first structural unit, the second structural unit, and the third structural unit, the molar content of the first structural unit is denoted as a%, the molar content of the second structural unit is denoted as b%, and the molar content of the third structural unit is denoted as c%; the silicone particles satisfy one or more of conditions (1) to (3): (1) 5 ≤ a / b ≤ 10; (2) 6≤a / c≤15; (3)a:b:c is (14-16):(3-4):(1-4).

12. The isolation film according to any one of claims 1 to 11, wherein: The organic material includes organic silicon particles, and the organic silicon particles include a second polymer, and the second polymer includes a structural unit represented by formula (a): In formula (a), R 14 and R 15 are each independently selected from substituted or unsubstituted C1-C10 alkyl, hydroxyl or amino; optionally, R 14 and R 15 Each is independently selected from substituted or unsubstituted C1-C6 alkyl, hydroxyl or amino; Optionally, the second polymer includes one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane, and polymethylaminosiloxane.

13. The isolation film according to any one of claims 9 to 12, wherein: The number average molecular weight of the organosilicon particles is 25000-60000, and can be optionally 30000-50000.

14. The isolation film according to any one of claims 9 to 13, wherein: The moisture content of the organic silicon particles is less than or equal to 3000 μg / g based on the mass of the organic silicon particles; The range can be selected from 700 μg / g to 2500 μg / g.

15. The isolation film according to any one of claims 9 to 14, wherein: The volume distribution particle size Dv90 of the organosilicon particles satisfies: Dv90≤4.0 μm; optionally, 0.5 μm≤Dv90≤3.0 μm; Optionally, the volume distribution particle size Dv50 of the organosilicon particles satisfies: 1.0 μm≤Dv50≤2.5 μm; Optionally, the particle size distribution of the organosilicon particles satisfies: 0.5≤(D V 90-D V 10) / D V 50≤1.

5.

16. The isolation film according to any one of claims 9 to 15, wherein: The specific surface area of ​​the organic silicon particles is less than or equal to 35 m 2 / g; 5m is optional 2 / g-30m 2 / g.

17. The isolation film according to any one of claims 1 to 16, wherein: The thickness of the substrate is less than or equal to 12 μm, and can be 3 μm-8 μm; and / or, The substrate has a porous structure, and the porosity of the substrate is greater than or equal to 20%, and can be optionally 25%-45%.

18. The isolation film according to any one of claims 1 to 17, wherein: The isolation film satisfies at least one of the following characteristics: (1) The longitudinal heat shrinkage of the isolation film at 150°C for 1 hour is less than or equal to 3%; (2) The transverse heat shrinkage of the isolation film at 150° C. for 1 hour is less than or equal to 2%; (3) The air permeability of the isolation membrane is less than or equal to 200s / 100mL, and can be 150s / 100mL-200s / 100mL; (4) The longitudinal tensile strength of the separator is greater than or equal to 2700 kgf / cm 2 ; (5) The transverse tensile strength of the separator is greater than or equal to 2500 kgf / cm 2 .

19. A method for preparing the isolation film according to any one of claims 1 to 18, comprising the following steps: Providing a substrate; The granular organic material is mixed in a solvent to prepare a coating slurry; Applying the coating slurry on at least one side of the substrate to form a slurry film layer, and drying the film layer to form a coating to obtain an isolation film; The weight per unit area of ​​the coating on one side is recorded as M, the thickness of the coating on one side is recorded as H, and the true density of the organic material is recorded as ρ 有机 , then the isolation film satisfies: M / (H×ρ 有机 )≥0.4, where the unit of M is g / m 2 , H is in μm, ρ 有机 The unit is g / cm 3 . 20 . A secondary battery comprising the separator according to claim 1 or the separator obtained by the preparation method according to claim 19 .

21. An electrical device comprising the secondary battery according to claim 20.